MIGRATION <<CAPITAL ECONOMIQUE>> DES MIGRANTS EN AFRIQUE DE L’OUEST: LE CAS DES MIGRANTS BURKINABE EN CÔTE D’IVOIRE - Noe, Atsain (European Scientific Journal, ESJ, 2015)
One of the factors of migration or immigration is the integration of migrants through the acquisition of social and economic position in a national space and country. With this integration of young Burkinabe come to live in Ivory Coast and perform income-generating activities. These departures are from the settlement were within the framework of the plantation work. Today they are experiencing changes and immigrants active in all sectors in Côte d’Ivoire. Indeed, this increase in migration or immigration representing very large sums is a comfort to his people, their families and their country. In this perspective, migrant transfers are estimated to billions of CFA francs.